2000
DOI: 10.1530/eje.0.1420231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thyrotoxicosis on adrenocortical reserve

Abstract: Objective: Variations in thyroid function are known to be associated with changes in adrenocortical activity. Previous studies in animals have suggested that long-standing hyperthyroidism may be associated with diminished adrenal functional reserve despite a continuing hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis. In humans, there has been no direct assessment of adrenal secretory reserve in clinical thyrotoxicosis. This study aimed to assess adrenocortical reserve in response to low-dose ACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 20 publications
2
62
1
1
Order By: Relevance
“…Glucocorticoid administration prevents adrenal crisis, as there is a potentially limited adrenal reserve in this acute setting. It also decreases the T4 to T3 conversion and in patients with Grave's disease may have an effect on the underlying autoimmune disease process (18). In patients who fail medical therapy, therapeutic plasma exchange is an option (19).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid administration prevents adrenal crisis, as there is a potentially limited adrenal reserve in this acute setting. It also decreases the T4 to T3 conversion and in patients with Grave's disease may have an effect on the underlying autoimmune disease process (18). In patients who fail medical therapy, therapeutic plasma exchange is an option (19).…”
Section: Discussionmentioning
confidence: 99%
“…Tsatsoulis et al [12] have recently demonstrated a subtle impairment in the cortisol response to ACTH stimulation in patients with thyreotoxicosis, indicating a diminished adrenocortical reserve. The increase in cortisol following treatment with thiamazole may therefore reflect a normalization of the adrenocortical function following normalization of the thyroid status.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data in rat models suggest that experimentally induced thyrotoxicosis is associated with altered HPA axis regulation: basal and ACTH-stimulated plasma corticosterone levels are increased in short-term experimental thyrotoxicosis, whereas in long-term thyroid hormone excess an attenuated corticosterone response to ACTH was observed [51][52][53][54] .…”
Section: Thyroid Function Stress and Immune Responsementioning
confidence: 99%